The Constitution’s Peoples: Approaching Community in the Context of Section 35 of the Constitution Act, 1982 - Olthuis, Brent (McGill Law Journal / Revue de droit de McGill, 2009)
Modern negotiations between the Crown (or private parties) and Canada’s Aboriginal peoples are largely based on the legal principles articulated in major court decisions. Yet those decisions have not yet confronted a fundamental question: how, in the first instance, do we determine which groups can lay claim to the Aboriginal and treaty rights “recognized and affirmed” by section 35 of the Constitution Act, 1982?